Multimedia pembelajaran berbasis web pada mata pelajaran akuntansi SMA untuk peningkatan motivasi dan hasil belajar - Chezaria Danaswari; Abdul Gafur (Jurnal Inovasi Teknologi Pendidikan, 2018)
Penelitian ini bertujuan menghasilkan multimedia pembelajaran berbasis web untuk mata pelajaran  Akuntansi SMA, dan mengetahui hasil belajar dan motivasi belajar dengan menggunakan multimedia pembelajaran berbasis web yang dikembangkan. Model pengembangan multimedia web menggunakan Alessi and Trollip melalui tiga tahapan, yakni perencanaan, desain, dan pengembangan. Uji coba evaluasi produk terdiri atas: evaluasi formatif meliputi uji alpha, yakni validasi produk oleh dua ahli materi dan dua ahli media, dan uji beta kesan siswa. Serta evaluasi sumatif meliputi uji coba hasil belajar dan motivasi belajar. Hasil penelitian menunjukkan: (1) produk yang dihasilkan berupa website studioakuntansi.com layak digunakan dalam kegiatan pembelajaran berdasarkan hasil penilaian ahli materi, ahli media dan uji beta dengan skor 4,23 (kategori sangat baik); (2) peningkatan skor rata-rata pada pretest dan posttest hasil belajar seluruh siswa sebesar 0,43 (kategori sedang), peningkatan skor rata-rata pada pretest dan posttest motivasi belajar seluruh siswa sebesar 0,38 (kategori sedang). Terdapat peningkatan hasil belajar dan motivasi belajar siswa setelah menggunakan multimedia pembelajaran  Akuntansi berbasis web.Kata kunci: pengembangan multimedia, pembelajaran berbasis web, multimedia web, pembelajaran  Akuntansi WEB BASED TEACHING MULTIMEDIA IN ACCOUNTING SUBJECT OF SENIOR HIGH SCHOOL FOR INCREASING MOTIVATION AND LEARNING OUTCOMESAbstractThe aims of this research are: (1) to produce web based teaching multimedia for accounting subject of senior high school (2) to find out the learning outcome and motivation by using web based teaching multimedia. The development of web based multimedia used Alessi and Trollip model consisting of three main phases: planning, design, developing. The product testing was held on: formative evaluation consisted of alpha testing involving validation by two subject material experts and two media experts, and beta testing of learners’ reaction, and sumative evaluation consisted of students’ learning outcome and motivation testing. The results of the research showed that: (1) the developed product was studioakuntansi.com website consisting of web based teaching multimedia in the accounting subject feasible to be used in classroom teaching and learning processes, based on the assessment by the subject material experts, media experts and also from the beta testing with the score of 4.23 (very good category), (2) the average gain score on the pretest and posttest of all students’ outcome was 0.43 (middle category), and the average gain score on the pretest and posttest of all students’ motivation was 0.38 (middle category). There was an increase on the students’ learning outcome and motivation after the use of the developed multimedia for accounting subject of senior high school.Keywords: multimedia development, web based learning, multimedia web, accounting subject